Translinguagem na educação bilíngue : uma análise das interações orais no 5° ano escolar - Morais, Maryvone Cunha de (2022)
The present study is based on a heteroglossic perspective that sees languages not as independent subsystems, but as integrated and dependent ones, linked to their sociocultural contexts. Considering that translanguaging (TL) has been extensively studied in multilingual geographic areas where the language of instruction is the language majority and less studied in contexts where the language of instruction is the minority language, the main objective of this thesis is to present and discuss the theoretical foundations of TL and analyze the use of the linguistic repertoire of children in the 5th year of Elementary School immersed in bilingual education. Our hypothesis is that TL is valid for contexts such as the Brazilian one due to its potential to transform the bilingual educational system by valuing the linguistic repertoire of students, endeavoring biliteracy. Two studies were developed: a systematic review (Study 1) that aimed to explore how investigations with TL have been conducted, and an experimental study (Study 2), which explored the attitudes and perceptions of students and their teachers towards TL, as well as investigated how those pupils manifest their translanguaging practices (TP) in an oral production of a narrative based on a non-verbal stimulus. In Study 2, Linguistic Questionnaires for Characterization and Use (QLCU) were administered to the three teachers and 14 students (7 pairs) to profile them regarding emerging TP in the classroom. Yet the collection of linguistic data was carried out through the production of an oral narrative based on a nonverbal video by seven pairs of students. The systematic review, which analyzed 24 remaining articles after applying the inclusion criteria, showed that TP have been investigated in written, oral, and written and oral tasks jointly, mainly through observation of interactions. The review showed that the TL research methods are under development, and it suggested different pedagogical implications based on the vision of languages integrated in a unitary repertoire. In Study 2, the results of the QLCU revealed that there was a solid stance towards keeping languages separate in formal contexts, which contrasted with a positive attitude towards multilingual behavior. Although students and teachers prefer to use the target language, TP were manifested in the classroom and during the execution of the oral task. Thus, both groups sought for a deeper biliteracy development. Post hoc analysis of students’ interactions during the oral task showed that TP with the use of gestures were frequent, followed by meaning negotiation, task management, lexical creativity, syntactic translanguaging, peer correction and form negotiation. In light of these results, we postulate that translanguaging pedagogy is valid for contexts of minority language development, in which educators are committed to promoting the TL corriente to provide biliteracy by valuing the unitary semiotic repertoire of the emergent bilinguals.